2007
DOI: 10.1680/geot.2007.57.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the time-dependent behaviour of rockfill

Abstract: Long-term strain records obtained in large-diameter oedometer tests on compacted gravels demonstrated that strains could be linearly related with the logarithm of time. Delayed compressibility coefficients were found proportional to the conventional stress-induced compressibility coefficients. A framework rooted on the phenomenon of crack propagation in rock particles induced by stress corrosion mechanisms is adopted to explain macroscopic observations. A model of crack propagation in loaded disc-shaped partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(75 citation statements)
references
References 27 publications
7
67
0
1
Order By: Relevance
“…Thus, the pH in the humid environment as well as the presence of other chemical components near the crack tips may serve to increase the speed of stress corrosion (Wiederhorn, 1975). Oldecop and Alonso (2007) investigated the eŠect of water on the time-dependent behavior of rockˆll and they found that the settlement of rockˆll dams with time could be understood in terms of the water-enhanced static fatigue of the rockˆll.…”
Section: Environmental Ešectsmentioning
confidence: 99%
“…Thus, the pH in the humid environment as well as the presence of other chemical components near the crack tips may serve to increase the speed of stress corrosion (Wiederhorn, 1975). Oldecop and Alonso (2007) investigated the eŠect of water on the time-dependent behavior of rockˆll and they found that the settlement of rockˆll dams with time could be understood in terms of the water-enhanced static fatigue of the rockˆll.…”
Section: Environmental Ešectsmentioning
confidence: 99%
“…proposed by Oldecop and Alonso (2007), where de is the strain increment and t the time measured at each loading step. The values obtained for some of tests performed on compacted marls are presented in Fig.…”
Section: Suction Controlled Tests On Marl Compacted Aggregatesmentioning
confidence: 99%
“…Unbound granular materials (unbound GMs) (e.g., unbound sands and gravels) may exhibit signiˆcant ratedependent behaviour (including signiˆcant creep deformation) inˆeld full-scale cases (e.g., Tatsuoka et al, 2000Tatsuoka et al, , 2001; Jardine et al, 2005Jardine et al, , 2006; Oldecop and Alonso, 2007). A number of laboratory stress-strain tests showed that unbound GMs have signiˆcant viscous properties and their trend is similar to that of saturated clays and bound materials (i.e., sedimentary soft rocks and cement-mixed soils) (e.g., Yamamuro among many others).…”
Section: Introductionmentioning
confidence: 99%